In the Cause of Liberty : How the Civil War Redefined American Ideals - McCardell, John; Cooper, William J., Jr. (William James), 1940- (Book collections on Project MUSE., 2009)
In this remarkable collection, ten premier scholars of nineteenth-century America address the epochal impact of the Civil War by examining the conflict in terms of three Americasantebellum, wartime, and postbellum nations. Moreover, they recognize the critical role in this transformative era of three groups of Americanswhite northerners, white southerners, and African Americans in the North and South. Through these differing and sometimes competing perspectives, the contributors address crucial ongoing controversies at the epicenter of the cultural, political, and intellectual history of thi.